Liquidity spillover effects of equity offerings over dual-class shares (2014)
We study the spillover effect from equity offerings over dual-class shares. Whereas, evidence has been found that a seasoned equity offering improves stock liquidity, the effect over the liquidity of different type shares of the same firm has not been explored. We use equity offerings of five Latin American countries: Brazil, Chile, Colombia, Mexico and Peru, during 1995 to 2012, because dual-class shares are widely used in the regions. In spite of the expected information asymmetry reduction, using panel data models we found a stock liquidity reduction of dual-class shares upon the offering; consistent with trading migration effects, according with the theory of inventory costs.